Impact of Microfinance in Agriculture and Livestock Production; Insights from Central Nepal - Sapkota, D.; Subedi, S.; Dhungana, S.M. (Journal of Agriculture and Environment, 2022)
This paper examines the impact of microfinance in agriculture and livestock in Dhading and Chitwan districts of Nepal. Municipalities within the districts were selected purposefully, and 60 respondents from each district were selected by simple random sampling method to comprise 120 respondents. The study showed significantly higher percentage of people participating in microfinance had self-sufficient food production. Probit regression analysis was done to estimate the impact of different predictor variables on farmer’s participation in microfinance. Although the production, income and gross margin of rice and wheat and gross margin of livestock was found statistically higher among the farmers participating in microfinance, the expense for rice and wheat was also found significantly higher among the farmers participating in microfinance. The result of Probit regression analysis showed six variables namely age of household head, caste/ethnicity, education of household head, agricultural credit, livestock unit (LSU), and annual household income were statistically significant for farmer’s participation in microfinance.